Structured Operations Training and Evaluation: A Case Study - Challacombe, Darin (International Journal of Advanced Corporate Learning (iJAC), 2024)
Onboarding for a company with remote, hybrid, and in-office workers can be challenging, especially if the workers are spread across the United States. This case study examines a US-based medical records company. This company met with stakeholders and developed a structured onboarding process which was implemented in December 2021. The case study follows employees who started between January and December 2022, analyzing their improvement in 30-, 60-, and 90-day assessments as well as their retention. While the data do not support a statistically significant increase, this process anecdotally improved the onboarding experience for new employees.